Activation of hepatic estrogen receptor-α increases energy expenditure by stimulating the production of fibroblast growth factor 21 in female mice - Camille Allard; Fabrice Bonnet; Beibei Xu; Laurel Coons; Diana Albarado; Cristal Hill; Guy Fagherazzi; Kenneth S. Korach; Ellis R. Levin; John Lefante; Christopher Morrison; Franck Mauvais-Jarvis (Elsevier, 2019)
Objective: The endogenous estrogen 17β-estradiol (E2) promotes metabolic homeostasis in premenopausal women. In a mouse model of post-menopausal metabolic syndrome, we reported that estrogens increased energy expenditure, thus preventing estrogen deficiency-induced adiposity. Estrogens' prevention of fat accumulation was associated with increased serum concentrations of fibroblast growth factor 21 (FGF21), suggesting that FGF21 participates in estrogens' promotion of energy expenditure. Methods: We studied the effect of E2 on FGF21 production and the role of FGF21 in E2 stimulation of energy expenditure and prevention of adiposity, using female estrogen receptor (ER)- and FGF21-deficient mice fed a normal chow and a cohort of ovariectomized women from the French E3N prospective cohort study. Results: E2 acting on the hepatocyte ERα increases hepatic expression and production of FGF21 in female mice. In vivo activation of ERα increases the transcription of Fgf21 via an estrogen response element outside the promoter of Fgf21. Treatment with E2 increases oxygen consumption and energy expenditure and prevents whole body fat accumulation in ovariectomized female WT mice. The effect of E2 on energy expenditure is not observed in FGF21-deficient mice. While E2 treatment still prevents fat accumulation in FGF21-deficient mice, this effect is decreased compared to WT mice. In an observational cohort of ovariectomized women, E2 treatment was associated with lower serum FGF21 concentrations, which may reflect a healthier metabolic profile. Conclusions: In female mice, E2 action on the hepatocyte ERα increases Fgf21 transcription and FGF21 production, thus promoting energy expenditure and partially decreasing fat accumulation. Keywords: Estrogen, ERα, FGF21, Menopause, Obesity, Metabolic syndrome